RP-HPLC simultaneous quantification of rutin, avobenzone, and octyl methoxycinnamate in the presence of hydroxypropyl β-cyclodextrin (HPβCD) and sulfobutyl ether β-cyclodextrin (SBEβCD) - Tércio Elyan Azevedo Martins; Claudinéia Aparecida Sales de Oliveira Pinto; Andressa Costa de Oliveira; Fabiana Vieira Lima; Maria Valéria Robles Velasco; Letícia Norma Carpentieri Rodrigues; André Rolim Baby (Universidade de São Paulo, 2023)
Abstract Development and validation of a simple and fast method of high-performance liquid chromatography with diode array detection (HPLC-DAD) for the simultaneously analysis of rutin, avobenzone, and octyl p-methoxycinnamate is presented. These substances were separated using a Kromasil C18 (250×4.6 mm, 5 μm) column, methanol: water (88:12 v/v) as the mobile phase, and a flow rate of 0.8 mL min−1. The experiment was performed at room temperature and elution was under isocratic conditions. Quantification was performed by external calibration at the wavelength of 325 nm. The validated parameters included linearity, selectivity, precision (repeatability), intermediate precision, accuracy, limit of detection, limit of quantification and robustness. The results of validation were statistically treated using the Action Stat version 3.5.152.34. The selectivity was also evaluated in the presence of two cyclodextrins (2-hydroxypropyl-β-cyclodextrin and β-cyclodextrin sulfobutyl ether sodium). The absence of parallelism between the curves of octyl p-methoxycinnamate in the absence and presence of the β-cyclodextrin sulfobutyl ether sodium in the mobile phase revealed interference from this matrix, thereby indicating the necessity of validating the method in the presence of this, and other matrices. The proposed method was selective, linear, precise, accurate, and robust for the simultaneous determination of rutin, avobenzone, and octyl p-methoxycinnamate.